2015
DOI: 10.1371/journal.pone.0125820
|View full text |Cite
|
Sign up to set email alerts
|

A Home-Based Educational Intervention Improves Patient Activation Measures and Diabetes Health Indicators among Zuni Indians

Abstract: IntroductionOne in three people will be diagnosed with diabetes by 2050, and the proportion will likely be higher among Native Americans. Diabetes control is currently suboptimal in underserved populations despite a plethora of new therapies. Patient empowerment is a key determinant of diabetes control, but such empowerment can be difficult to achieve due to resource limitation and cultural, language and health literacy barriers. We describe a home-based educational intervention using Community Health Represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 37 publications
1
69
0
Order By: Relevance
“…Prior interventional studies for chronic disease have had similar outcomes in terms of patient activation. A home-based educational intervention for native Americans with type 2 diabetes by Shah et al 25 found a significant increase in patient activation. Another self-management intervention for diabetic patients in Norwegian primary care demonstrated a persistent increase in their level of activation 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior interventional studies for chronic disease have had similar outcomes in terms of patient activation. A home-based educational intervention for native Americans with type 2 diabetes by Shah et al 25 found a significant increase in patient activation. Another self-management intervention for diabetic patients in Norwegian primary care demonstrated a persistent increase in their level of activation 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the single site study limits results' generalizability. This study design—frequently adopted in research testing the feasibility and potential impact of educational interventions (Hulsman et al, 1999; Berger et al, 2010; Lamiani et al, 2011; Meyer et al, 2011; Bartels et al, 2013; Ledford et al, 2014; Arnold et al, 2015; Shah et al, 2015; Robinson et al, 2016; Viau et al, 2016) is appropriate for the demonstration of feasibility and for initial proof of concept, it is cost effective, and it is pragmatic because it allows for “real world” variability in variables. Consistent with the intent of a pilot study, our goal was to examine feasibility and potential impact.…”
Section: Discussionmentioning
confidence: 99%
“…16 Both education and health literacy are strongly linked to racial disparities and health promotion; 20 however, the association of either of these two factors with patient activation are less well-described. 2123 …”
mentioning
confidence: 99%